Juridical Analysis of the Practice of Child Marriage in the Onto Village, Bantaeng Regency - Izzah, Ibnu (Jurnal Al-Qadau: Peradilan dan Hukum Keluarga Islam, 2022)
This study examines the analysis of Islamic Law and National Law in addressing the practice of Child Marriage that occurred in the Onto Village, Bantaeng Regency. The purpose of this research is to build synergy between the Islamic Family Law study program and the local government regarding the prevention of child marriage and provide education regarding the ideal minimum age for marriage from a legal and health perspective. This type of research is field research with data collection methods, observation, documentation and interviews with several parties concerned directly with the object of this research. Research data were obtained from two sources, namely interviews, legal counselling, and questionnaires which are the primary data sources. While the second is books, journals, and literature related to marriage which are secondary data sources in this study. The results of this study indicate that child marriage that occurs in the Onto Village community is dilator due to several factors, namely the lack of public understanding regarding the minimum age limit for marriage regulated in law, as well as the psychological and reproductive health impacts, especially for the bride, and also economic factors. So that the implications of this research will give birth to the dissemination of ideal marriage to the community along with the development of child psychology and the dynamics of existing laws. Keywords: Islamic Law, National Law, Child Marriage